The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1113/jphysiol.2004.063768
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein and ATP/ADP carrier increase mitochondrial proton conductance after cold adaptation of king penguins

Abstract: Juvenile king penguins develop adaptive thermogenesis after repeated immersion in cold water. However, the mechanisms of such metabolic adaptation in birds are unknown, as they lack brown adipose tissue and uncoupling protein-1 (UCP1), which mediate adaptive non-shivering thermogenesis in mammals. We used three different groups of juvenile king penguins to investigate the mitochondrial basis of avian adaptive thermogenesis in vitro. Skeletal muscle mitochondria isolated from penguins that had never been immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 46 publications
6
122
3
4
Order By: Relevance
“…The ability of HCF1 pretreatment to partially reverse the mitochondrial GSH depletion induced by I/R challenge likely involved the upregulation of cellular glutathione redox cycling through the intermediacy of mitochondrial ROS production, as was the case in H9c2 cardiomyocytes (Yim & Ko, 1999;Ramires & Ji, 2001). While the reduction of tissue ATP level by long-term, low-dose HCF1 pretreatment in non-I/R rat hearts might be due to the induction of a sustained mitochondrial uncoupling, the significant reduction of tissue ATP level in ischemic/reperfused rat hearts was likely due to the impaired mitochondrial electron transport and oxidative phosphorylation (Talbot et al, 2004;Brennan et al, 2006). The reduced extent of I/Rinduced myocardial ATP depletion in HCF1-pretreated rat hearts, as observed in the present study, was likely related to the increased ATP-GC that compensated the enhanced ATP consumption for cellular homeostasis during reperfusion (Plaschke et al, 1998;Young, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of HCF1 pretreatment to partially reverse the mitochondrial GSH depletion induced by I/R challenge likely involved the upregulation of cellular glutathione redox cycling through the intermediacy of mitochondrial ROS production, as was the case in H9c2 cardiomyocytes (Yim & Ko, 1999;Ramires & Ji, 2001). While the reduction of tissue ATP level by long-term, low-dose HCF1 pretreatment in non-I/R rat hearts might be due to the induction of a sustained mitochondrial uncoupling, the significant reduction of tissue ATP level in ischemic/reperfused rat hearts was likely due to the impaired mitochondrial electron transport and oxidative phosphorylation (Talbot et al, 2004;Brennan et al, 2006). The reduced extent of I/Rinduced myocardial ATP depletion in HCF1-pretreated rat hearts, as observed in the present study, was likely related to the increased ATP-GC that compensated the enhanced ATP consumption for cellular homeostasis during reperfusion (Plaschke et al, 1998;Young, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the loss of the phylogenetic and allometric differences in proton conductance found with liposomes made from the mitochondrial membrane (Brookes et al, 1997) further highlights that the presence of mitochondrial membrane proteins plays an important role in determining proton permeability (Stuart et al, 2001). For example, this has been suggested for the content of adenine nucleotide translocase (Talbot et al, 2004;Brand et al, 2005;Shabalina et al, 2006). In amphibians, some studies have shown that the mitochondrial inner membrane surface area might be greater in the mitochondria of liver and muscle from smaller species (Brookes et al, 1998;Hulbert et al, 2006;Berner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of avUCP in cold-acclimated ducklings [24], chickens [25] and king penguins [26] has been demonstrated. Moreover, we also reported the negative correlation between avUCP content and mitochondrial superoxide production in chicken skeletal muscle during acute heat stress [27].…”
Section: Introductionmentioning
confidence: 96%